The Advantage of Supine and Standing Heart Rate Variability Analysis to Assess Training Status and Performance in a Walking Ultramarathon - Maggioni, Martina Anna; Rundfeldt, Lea Christiane; Gunga, Hanns-Christian; Joerres, Marc; Merati, Giampiero; Steinach, Mathias (Frontiers in Physiology, 2020)
Cardiac autonomic modulation of heart rate, assessed by heart rate variability (HRV), is commonly used to monitor training status. HRV is usually measured in athletes after awakening in the morning in the supine position. Whether recording during standing reveals additional information compared to supine remains unclear. We aimed to evaluate the association between short-duration HRV, assessed both in the supine and standing position, and a low-intensity long-duration performance (walking ultramarathon), as well as training experience. 25 competitors in a 100 km walking ultramarathon underwent pre-race supine (12 min) and standing (6 min) HR recordings, whereas performance and subjective training experience were assessed post-race. There were no significant differences in both supine and standing HRV between finishers (n = 14) and non-finishers (n = 11, mean distance 67 km). In finishers, a slower race velocity was significantly correlated with a higher decrease in parasympathetic drive during position change [larger decrease in High Frequency power normalized units (HFnu: r -0.7, p 0.01) and higher increase in the detrended fluctuation analysis alpha 1 index (DFA1: r 0.6, p 0.04)]. Highly trained athletes accounted for higher HFnu during standing compared to poorly trained competitors (+11.5, p 0.01). Similarly, greater training volume (total km/week) would predict higher HFnu during standing (r 0.5, p 0.01). HRV assessment in both supine and standing position may provide additional information on the dynamic adaptability of cardiac autonomic modulation to physiologic challenges and therefore be more valuable for performance prediction than a simple assessment of supine HRV. Self-reported training experience may reliably associate with parasympathetic drive, therefore indirectly predicting long-term aerobic performance in ultramarathon walking races.